2010
DOI: 10.1016/j.jsat.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of alcohol pharmacotherapies in the Clinical Trials Network: The influence of research network participation

Abstract: Organizational participation in clinical research may lead to adoption of the intervention by treatment agencies, but it is not known whether research involvement enhances innovativeness beyond the specific interventions that are tested. The National Institute on Drug Abuse's (NIDA) Clinical Trial Network (CTN) is a platform for considering this research question. To date, the CTN has not conducted research on medications for alcohol use disorders (AUDs), so greater adoption of innovative AUD pharmacotherapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…Further, if the implementation of pharmacotherapy still requires substantial co-payments, the projected advantages in terms of improvement in treatment quality by providing access to more treatment options may be lost (Capoccia et al, 2012). As expected, the employment of physicians on staff at baseline was positively associated with the likelihood that organizations made the transition to medication adoption, consistent with our prior cross-sectional research (Abraham et al, 2010;Knudsen et al, 2007Knudsen et al, , 2010. Because of our use of a lagged dependent variable, however, our data do not provide in-depth information regarding whether an expansion of medical capabilities preceded or followed the decision to adopt pharmacotherapy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, if the implementation of pharmacotherapy still requires substantial co-payments, the projected advantages in terms of improvement in treatment quality by providing access to more treatment options may be lost (Capoccia et al, 2012). As expected, the employment of physicians on staff at baseline was positively associated with the likelihood that organizations made the transition to medication adoption, consistent with our prior cross-sectional research (Abraham et al, 2010;Knudsen et al, 2007Knudsen et al, , 2010. Because of our use of a lagged dependent variable, however, our data do not provide in-depth information regarding whether an expansion of medical capabilities preceded or followed the decision to adopt pharmacotherapy.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on the availability of SUD pharmacotherapies in specialty treatment organizations have often focused on the diffusion of specifi c medications, such as buprenorphine, acamprosate, and naltrexone (Abraham et al, 2010Ducharme et al, 2006Ducharme et al, , 2007Friedmann et al, 2010;Koch et al, 2006;Roman, 2007, 2008;Roman et al, 2011;Savage et al, 2012;Thomas et al, 2003Thomas et al, , 2008. In addition, research has considered the organizational factors associated with the availability of any type of SUD medication Knudsen et al, 2010Knudsen et al, , 2011, in part because the adoption of at least one medication is correlated with offering other pharmacotherapies (Fuller et al, 2005).…”
mentioning
confidence: 99%
“…They included 12 of the 13 papers in Clarke and Loudon's review, [97][98][99][100][101][102]104,105,[108][109][110][111] and an additional 21 papers, 103,106,107,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] including 10 published since the beginning of 2009 [114][115][116][117][118][119]121,123,126,128 when Clarke and Loudon conducted their search. We had a broader remit and conducted our search in a different way, but we were able to benefit from knowing which papers they had included and ensuring that our search terms captured as many of these papers as possible.…”
Section: Chaptermentioning
confidence: 99%
“…[118][119][120][121][122][123][124][125] All eight come from the USA with three relating to various breast cancer networks, 119,122,125 three relating to the Clinical Trials Network (CTN) of the National Institute on Drug Abuse, 118,120,121 and two describing aspects of PBRNs. 123,124 Seven 118,119,[121][122][123][124][125] of these eight papers were positive about research engagement leading to health-care improvement, at least in terms of the processes of care. We classified four 118,119,121,122 of these studies as important, as we did one study 120 that reported more mixed findings, but with some positive claims about research engagement leading to improvements in health-care performance.…”
Section: Network Papersmentioning
confidence: 99%
See 1 more Smart Citation